(untitled) (Journal of Information Technology and Digital World, 2024)
Gamification, involving elements like earning points and badges, has emerged as a strategy to enhance user retention. This study investigates the impact of gamification on customer engagement and loyalty in the retail industry, addressing challenges in user retention for mobile apps. The objective comprises learning about gamification’s influence, exploring user satisfaction components, and offering recommendations. The study adopts a survey-based descriptive research approach in Bengaluru city, targeting prospective gamification-enabled app users. The study collected data from a sample of 116 participants in Bengaluru, Statistical analyses conducted using the Statistical Package for Social Sciences (SPSS) included descriptive statistics to profile the participants, factor analysis to identify key components influencing user experience, and Spearman’s rho correlation analysis to explore relationships between gamification, engagement, and user recommendations.